Análisis De Riesgo Ergonómico En Una Empresa Automotriz En México - Tapia, Luz del Carmen Sierra; Buenrostro, María Azucena Arellano; Cabrera, Josué Mauricio Becerra; Pérez, Juan Enrique Troncoso; Malagón, Genaro Vega (European Scientific Journal, ESJ, 2017)
OBJECTIVE: Analyze the ergonomic risk of the workers of an automotive company using the Check-List OCRA method. METHODOLOGY: An analytical cross-sectional study of the workers of an automotive company was carried out in a production area during the period from August to November 2015. A total of 17 evaluations were carried out based on the data collected from the analysis of the videos of each operation. The information was captured in the application for the OCRACheckINSHT v.1.2 Repetitive Work Risk Assessment, from which the final results were obtained, thus identifying the level of ergonomic risk. RESULTS: A total of 17 operations analyzed, 8 (23%) presented a high level of ergonomic risk, 12 (35%) were at an average ergonomic risk level, 3 (9%) were at a level of mild ergonomic risk, 6 (18%) at a very low ergonomic risk level and 5 (15%) are at an acceptable ergonomic risk level. The determinants of ergonomic risk were mainly posture, strength and frequency. CONCLUSIONS: In the production area analyzed, operations with high and medium ergonomic risk levels were found to be the highest percentage. Therefore it is necessary to implement pauses based on physical activity and stretching of upper limbs as prevention of musculoskeletal injuries as well as avoid monotony. Likewise, work rotation is suggested as a measure to prevent ergonomic injuries.